Bm-miR172c-5p Regulates Lignin Biosynthesis and Secondary Xylem Thickness by Altering the Ferulate 5 Hydroxylase Gene in Bacopa monnieri. (1st May 2021) - Jeena, Gajendra Singh; Joshi, Ashutosh; Shukla, Rakesh Kumar
Abstract: MicroRNAs (miRNAs) are small non-coding, endogenous RNAs containing 20–24 nucleotides that regulate the expression of target genes involved in various plant processes. A total of 1, 429 conserved miRNAs belonging to 95 conserved miRNA families and 12 novel miRNAs were identified from Bacopa monnieri using small RNA sequencing. The Bm-miRNA target transcripts related to the secondary metabolism were further selected for validation. The Bm-miRNA expression in shoot and root tissues was negatively correlated with their target transcripts. The Bm-miRNA cleavage sites were mapped within the coding or untranslated region as depicted by the modified RLM-RACE. In the present study, we validate three miRNA targets, including asparagine synthetase, cycloartenol synthase and ferulate 5 hydroxylase ( F5H ) and elucidate the regulatory role of Bm-miR172c-5p, which cleaves the F5H gene involved in the lignin biosynthesis. Overexpression (OE) of Bm-miR172c-5p precursor in B. monnieri suppresses F5H gene, leading to reduced lignification and secondary xylem thickness under control and drought stress. By contrast, OE of endogenous target mimics (eTMs) showed enhanced lignification and secondary xylem thickness leading to better physiological response under drought stress. Taken together, we suggest that Bm-miRNA172c-5p might be a key player in maintaining the native phenotype of B. monnieri under control and different environmental conditions.